Comparative Efficacy and Safety of Anti-PD-1/PD-L1 for the Treatment of Non-Small Cell Lung Cancer: A Network Meta-Analysis of 13 Randomized Controlled Studies - Jiang, Maofen; Liu, Chunjiao; Ding, Dongxiao; Tian, Hui; Yu, Chaoqun (Frontiers in Oncology, 2022)
Objective: The present network meta-analysis was conducted to summarize the direct and indirect evidence of common PD1/PDL1 inhibitors including avelumab, atezolizumab, cemiplimab, nivolumab and pembrolizumab for the treatment of NSCLC patients and further to determine the optimal therapeutic regime. Methods: We performed a systematic literature search to identify all potentially eligible studies in PubMed, Embase and the Cochrane library until to August 7, 2021. The primary outcome was overall survival, and the second outcome was treatment-related adverse events (TRAEs). We used random-effects model to conduct direct and network meta-analyses, which were performed by using RevMan 5.3 and R version 3.6.1, respectively. Results: Direct meta-analysis suggested that atezolizumab, cemiplimab, nivolumab, or pembrolizumab significantly improved OS compared with CT, and network meta-analysis further established that atezolizumab (HR, 0.77; 95% CrI, 0.62 to 0.96), nivolumab (HR, 0.75; 95% CrI, 0.62 to 0.93), or pembrolizumab (HR, 0.71; 95% CrI, 0.57 to 0.89) significantly and cemiplimab (HR, 0.68; 95% CrI, 0.46 to 1.02) numerically improved OS compared with CT. Meanwhile, network meta-analysis also indicated cemiplimab was numerically superior to other PD1/PD-L1 agents. Moreover, avelumab, atezolizumab, cemiplimab, nivolumab and pembrolizumab were found to have fewer TRAEs compared with CT in direct meta-analysis, which were supported by the results from network meta-analysis. Meanwhile, SUCRA and ranking probability suggested that cemiplimb provided the most favorable balance between efficacy and safety, with the first ranking for the OS. Conclusions: Based on available evidence, cemiplimb may have the most favorable risk-benefit ratio for NSCLC patients compared with other common therapeutic management. However, future research with large-scale, high-quality, and a mature follow-up, are needed to further determine which agents should be preferentially selected for NSCLC patients due to the limitations of our network meta-analysis and variations of eligible studies in treatment line and sPD-L1 status.